PENGARUH PENGUNGKAPAN EMISI KARBON DAN KINERJA LINGKUNGAN TERHADAP REAKSI INVESTOR DENGAN MEDIA EXPOSURE SEBAGAI VARIABEL MODERASI - Sanggi Asyari (2023)
The purpose of this study was to determine the effect of disclosure of carbon emissions and environmental performance on investor reactions by knowing the relationship between disclosure of carbon emissions and environmental performance on investor reactions. The population used were manufacturing companies in the food and beverage industry sub-sector, the cement sub-sector, and the tobacco sub-sector which were listed on the Indonesia Stock Exchange in 2018, 2019 and 2020. The number of samples in this study was 63, using the purposive sampling method and secondary data, reports Annually obtained from IDX website and issuers. The analytical method used is multiple linear regression analysis. The results of the study show that disclosure of carbon emissions has a significant negative effect on investor reactions. This is due to the low perception of investors regarding disclosure of carbon emissions, and is only considered as an advertisement. Meanwhile, environmental performance has a significant positive effect on investor reactions. Bad news media exposure weakens disclosure of carbon emissions to investor reactions, while bad news media exposure strengthens environmental performance to investor reactions.